1989
DOI: 10.1111/j.1525-1314.1989.tb00579.x
|View full text |Cite
|
Sign up to set email alerts
|

Thermal model for the Zanskar Himalaya

Abstract: Crustal thickening along the northern margin of the Indian plate, following the 50 Ma collision along the Indus Suture Zone in Ladakh, caused widespread high-temperature, medium-pressure Barrovian facies series metamorphism and anatexis. In the Zanskar Himalaya metamorphic isograds are inverted and structurally telescoped along the Main Central Thrust ( M m ) Zone at the base of the High Himalayan slab. Along the Zanskar valley at the top of the slab, isograds are the right way-up and are also telescoped along… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
142
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 191 publications
(145 citation statements)
references
References 19 publications
3
142
0
Order By: Relevance
“…Searle & Rex 1989;Hodges et al 1992;Harrison et al 1998;Searle et al 1999b). Several recent papers interpreted the structural and thermal data from the GHS in terms of a channel flow model, whereby the middle crust was extruded southwards between coeval thrust-and normalsense shear zones (Grujic et al 1996(Grujic et al , 2002Beaumont et al 2001Beaumont et al , 2004Searle et al 2002Searle & Szulc 2005).…”
Section: Greater Himalayan Sequencementioning
confidence: 99%
“…Searle & Rex 1989;Hodges et al 1992;Harrison et al 1998;Searle et al 1999b). Several recent papers interpreted the structural and thermal data from the GHS in terms of a channel flow model, whereby the middle crust was extruded southwards between coeval thrust-and normalsense shear zones (Grujic et al 1996(Grujic et al , 2002Beaumont et al 2001Beaumont et al , 2004Searle et al 2002Searle & Szulc 2005).…”
Section: Greater Himalayan Sequencementioning
confidence: 99%
“…7) developed for the Greater Himalaya along the southern margin of the Tibetan Plateau was proposed initially from field geological mapping and strain data combined with P-T constraints and U-Pb dating of metamorphic rocks and leucogranites (Searle & Rex 1989;Grujic et al 2002;Searle et al 2003Searle et al , 2006Law et al 2004Law et al , 2006Searle & Szulc 2005;Godin et al 2006). The channel flow model infers that a partially molten middle crust layer was extruded south from beneath southern Tibet to the Greater Himalaya during the Early Miocene, at c. 23-15 Ma.…”
Section: Himalayan Channel Flow Modelsmentioning
confidence: 99%
“…The geologically constrained parameters include a 10-20 km thick middle crust composed of sillimanite-K-feldspar grade gneisses, migmatites and leucogranites bounded by an inverted metamorphic sequence above the Main Central Thrust along the base and a right-way-up metamorphic sequence beneath a major low-angle normal fault, the South Tibetan Detachment, along the top (Searle et al , 2010b. From mapping of metamorphic isograds in western Zanskar and eastern Kashmir, Searle & Rex (1989) showed that the isograds are folded around a large-scale SW-verging recumbent fold with c. 100 km of SW displacement along both ductile shear zones along the top (South Tibetan Detachment zone) and bottom (Main Central Thrust zone). Both the Main Central Thrust and the South Tibetan Detachment are major ductile shear zones active synchronously during the Early Miocene (c. 24-15 Ma) when the partially molten middle crust was extruded southward at least 100 km beneath the brittle deforming upper crust of southernmost Tibet (Indian plate Tethyan or Northern Himalaya).…”
Section: Himalayan Channel Flow Modelsmentioning
confidence: 99%
“…This is in part due to the relative paucity of index minerals in many sections of the STDS. Exceptions to this include Zanskar (Searle and Rex, 1989), the Sutlej Valley in NW India (Chambers and others, 2009) and the Everest region (e.g. Jessup and others 2008) and Bhutan (e.g.…”
Section: Discussionmentioning
confidence: 99%